Mouse Models Recapitulating Human Adrenocortical Tumors: What Is Lacking? - Leccia, Felicia; Batisse-Lignier, Marie; Sahut-Barnola, Isabelle; Val, Pierre; Lefrançois-Martinez, A-Marie; Martinez, Antoine (Frontiers in Endocrinology, 2016)
Adrenal cortex tumors are divided into benign forms such as primary hyperplasias and adrenocortical adenomas (ACAs), and malignant forms or adrenocortical carcinomas (ACCs). Primary hyperplasias are rare causes of ACTH-independent hypercortisolism. ACAs are the most common type of adrenal gland tumors and they are rarely “functional”, i.e producing steroids. When functional, adenomas result in endocrine disorders such as Cushing’s syndrome (hypercortisolism) or Conn’s syndrome (hyperaldosteronism). In contrast, ACCs are extremely rare but highly aggressive tumors that may also lead to hypersecreting syndromes. Genetic analyses of patients with sporadic or familial forms of adrenocortical tumors led to the identification of potentially causative genes, most of them being involved in PKA, Wnt/β-catenin and P53 signaling pathways. Development of mouse models is a crucial step to firmly establish the functional significance of candidate genes, to dissect mechanisms leading to tumors and endocrine disorders and in fine to provide in vivo tools for therapeutic screens. In this article we will provide an overview on the existing mouse models (xenografted and genetically engineered) of adrenocortical tumors by focusing on the role of PKA and Wnt/β-catenin pathways in this context. We will discuss the advantages and limitations of models that have been developed heretofore and we will point out necessary improvements in the development of next generation mouse models of adrenal diseases.